Synthesis of novel Meerschaum (Sepiolite) derived bioceramics versus hydroxyapatite based bone grafts - Demirel, Mehtap; Aksakal, Bunyarnin (ELSEVIER SCI LTD, 2015)
Meerschaum Sepiolite derived bioceramics have been synthesised via the sol-gel method and were compared with nano (N) and micro (M) scale-hydroxyapatite (HA) based bone grafts. The newly fabricated Meerschaum (Sepiolite) bioceramic bone grafts were characterised by Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FITR) and X-ray Diffraction (XRD). The mechanical properties were determined through the Compression and Vickers hardness tests. Significant differences were observed in the FTIR spectrography of the samples as Meerschaum (Sepiolite) addition increased in HA-based biografts. In the nano-scale-HA-based biografts and increase in Sepiolite ratio increased the porosity, In the micro-scale-HA based biografts, porosity decreased with increased Sepiolite ratio. However, compression strength was not found to deteriorate with Sepiolite additions. Overall, the results confirm the suitability of such graft materials for biomedical applications. (C) 2015 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Meerschaum Sepiolite; Hydroxyapatite; Sol-gel; Bone graft; CALCIUM-PHOSPHATE CEMENT; COMPRESSIVE STRENGTH; SUBSTITUTES; BEHAVIOR; FIBER; TCP; Materials Science